Metal-free Catalyzed One-Pot Multicomponent Synthesis of (E)-3-(2-((5-(Benzylideneamino)-1,3,4-thiadiazol-2-yl)thio) Acetyl)-2H-chromen-2-one Derivatives and Their Biological Evaluation - Shivanand Merugu; Vijaya Kumar Ponnamaneni; Ravi Varala; Syed Farooq Adil; Mujeeb Khan; Mohammed Rafiq H. Siddiqui; Ravikumar Vemula (Journal of Chemistry)
A series of (E)-3-(2-((5-(benzylideneamino)-1,3,4-thiadiazol-2-yl)thio) acetyl)-2H-chromen-2-one and its derivatives (4a-h) have been obtained using a one-pot multicomponent reaction with good yields. The compounds have been synthesized from 3-(2-bromoacetyl)chromen-2-ones (1), 5-amino-1,3,4-thiadiazole-2-thiol (2), and substituted benzaldehydes (3) in anhydrous ethanol and conc. H2SO4. Subsequently, all the synthesized compounds have been screened for their antimicrobial activity and characterized by analytical and spectral data.